2019
DOI: 10.1186/s13068-019-1544-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of biomass and lipids by Euglena gracilis via co-culturing with a microalga growth-promoting bacterium, Emticicia sp. EG3

Abstract: BackgroundEuglena gracilis, a unicellular flagellated microalga, is regarded as one of the most promising species as microalgal feedstock for biofuels. Its lipids (mainly wax esters) are suitable for biodiesel and jet fuel. Culture of E. gracilis using wastewater effluent will improve the economics of E. gracilis biofuel production. Enhancement of the productivity of E. gracilis biomass is critical to creating a highly efficient biofuels production system. Certain bacteria have been found to promote microalgal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 51 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…Previous reports have also indicated that the biomass and paramylon production of E. gracilis is increased when it is co-cultivated with the bacterium Pseudoalteromonas under optimal conditions, the extracellular polymeric substances (EPS) of the bacterium contributed to the results ( Jeon et al, 2019 , 2020 ). When co-cultivated with the microalga growth-promoting bacterium Emticicia , E. gracilis was found to have higher biomass and produce more lipids ( Toyama et al, 2019 ). Despite all of the beneficial effects found in these co-cultivation systems, the underlying mechanisms have not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have also indicated that the biomass and paramylon production of E. gracilis is increased when it is co-cultivated with the bacterium Pseudoalteromonas under optimal conditions, the extracellular polymeric substances (EPS) of the bacterium contributed to the results ( Jeon et al, 2019 , 2020 ). When co-cultivated with the microalga growth-promoting bacterium Emticicia , E. gracilis was found to have higher biomass and produce more lipids ( Toyama et al, 2019 ). Despite all of the beneficial effects found in these co-cultivation systems, the underlying mechanisms have not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, specific antagonistic organisms can be introduced to promote the synthesis of antibiotics (Bertrand et al, 2014;Romano et al, 2018;Bovio et al, 2019b). Enhanced lipid production in microalgae has been documented in co-cultivation of microalgae and bacteria, including cyanobacteria (Ferro et al, 2019;Gautam et al, 2019;Toyama et al, 2019), as well as in co-cultivation of microalgae and fungi (Arora et al, 2019). Growth-enhancement in microalgae has been documented in co-cultivation of microalgae with other microalgae (Ishika et al, 2019), as well as with fungi and protozoa (Peng et al, 2016).…”
Section: Biotechnological Production Of Secondary Metabolitesmentioning
confidence: 99%
“…Therefore, supplementation of these vitamins by scaling up cultivation, co-culturing E. gracilis and bacteria that produce the required nutrients, and production of transgenic E. gracilis , are a few solutions to overcome this problem ( Gissibl et al, 2019 ). Co-culturing microalgae and microalga growth-promoting bacteria (MGPB) is known to increase biomass production ( Fuentes et al, 2016 ; Ramanan et al, 2016 ; Toyama et al, 2019 ) Emticicia sp. EG3 was the first MGPB to be discovered and used in co-culture with E. gracilis , which enhanced the biomass production more than three-fold ( Toyama et al, 2019 ).…”
Section: Research Challenges Involved In the Genetic Modification Ofmentioning
confidence: 99%
“…Co-culturing microalgae and microalga growth-promoting bacteria (MGPB) is known to increase biomass production ( Fuentes et al, 2016 ; Ramanan et al, 2016 ; Toyama et al, 2019 ) Emticicia sp. EG3 was the first MGPB to be discovered and used in co-culture with E. gracilis , which enhanced the biomass production more than three-fold ( Toyama et al, 2019 ).…”
Section: Research Challenges Involved In the Genetic Modification Ofmentioning
confidence: 99%